Elechi Amadi's Women: Voices of Reason (Nordic Journal of African Studies, 2004)
This article assesses Elechi Amadi's novelistic attitude to gender relations in his novels of the 60s and 70s, when traditional African society was still very strongly male-dominated, and reaches the conclusion that he saw in the woman the real force of stability and progress. Through highly successful narrative incidents he demonstrates how women succeed where men stumble, especially in conflict resolution and home management. This view brings its relevance to bear on the present-day scene where attempts are made, both within the African milieu and on the international stage, to endow women with a new role. Amadi maintains that the women have always shaped society with their positive thinking, and that therefore their importance needs greater recognition, not re-invention.